2017
DOI: 10.1093/nar/gkx018
|View full text |Cite
|
Sign up to set email alerts
|

The CCTL (Cpf1-assisted Cutting and Taq DNA ligase-assisted Ligation) method for efficient editing of large DNA constructsin vitro

Abstract: As Cpf1 cleaves double-stranded DNA in a staggered way, it can be used in DNA assembly. However, the Cpf1 cleavage was found to be inaccurate, which may cause errors in DNA assembly. Here, the Cpf1 cleavage sites were precisely characterized, where the cleavage site on the target strand was around the 22nd base relative to the protospacer adjacent motif site, but the cleavage on the non-target strand was affected by the spacer length. When the spacer length was 20 nt or longer, Cpf1 mainly cleaved around the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 33 publications
2
73
0
Order By: Relevance
“…1B) [64,65]. In contrast to Cas9, Cas12a solely requires a small crRNA to mediate its activity, target specificity is determined by a longer spacer, requiring at least 22 nt for maximum efficiency [64,66]. Instead of G-rich PAMs required by Cas9, Cas12a recognizes T-rich PAMs and thus further increases the number of potential target sites.…”
Section: Using Cas12a (Formerly Named Cpf1) In Plantsmentioning
confidence: 99%
“…1B) [64,65]. In contrast to Cas9, Cas12a solely requires a small crRNA to mediate its activity, target specificity is determined by a longer spacer, requiring at least 22 nt for maximum efficiency [64,66]. Instead of G-rich PAMs required by Cas9, Cas12a recognizes T-rich PAMs and thus further increases the number of potential target sites.…”
Section: Using Cas12a (Formerly Named Cpf1) In Plantsmentioning
confidence: 99%
“…Previous work demonstrated that FnCas12a can perform DNA editing in vitro (Lei et al, ; S. Y. Li et al, ). However, limited PAM recognition restricts its application.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work demonstrated that FnCas12a can perform DNA editing in vitro (Lei et al, 2017;S. Y. Li et al, 2016).…”
Section: The Application Of Icope In Seamless Dna Editingmentioning
confidence: 99%
See 2 more Smart Citations